Memory: Conference on Human Rights and Peace in Colombia (Revista Investigación & praxis en CS Sociales, 2023)
This memory explores the intersection of peace, human rights, and democracy in Colombia through the academic perspective of experts such as Dr. Bernardo Nicolás Sánchez García and Professor Emeritus Jaime Zuluaga Nieto. It analyzes the historical evolution of peace and human rights, highlighting challenges and advances, including the conceptualization of peace as a human right. The Conference on Human Rights and Peace in Colombia examines violence in different periods and emphasizes the importance of bringing these issues to undergraduate students.
Keywords: Intersection; Peace; Human Rights; Democracy; Historical evolution